DEVELOPMENT OF A WEB-BASED POINT OF SALE APPLICATION US-ING THE LARAVEL FRAMEWORK - Apriani, Rika; Haerani, Reni; Nugroho, Praditya Adi; Farisi, Imam (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2025)
The development of information technology encourages businesses to take over digital systems in business operations, even in the sales process. The Point of Sales (POS) system is the leading solution for recording transactions, managing stock, and creating sales reports efficiently. This study aims to develop a POS application based on a website and make it easier for administrators to manage sales transactions, making them faster and more efficient. This system is made with a structured Agile method, requirements, design, development, testing, deployment, and implementation, and the framework used is the Laravel framework. The test results show that the system is on track and that the efficiency of the transaction and reporting process can be increased. A web-based basis allows users to manage their business more easily in real time because this application is flexible and can be used on various devices.            Keywords: Point of Sales; Laravel; Agile Model;Websites